Xanthohumol alleviates oxidative stress and impaired autophagy in experimental severe acute pancreatitis through inhibition of AKT/mTOR - Huangfu, Yaru; Yu, Xiuxian; Wan, Chengyu; Zhu, Yuda; Wei, Zeliang; Li, Fan; Wang, Yilan; Zhang, Kun; Li, Shiyi; Dong, Yuman; Li, Yangying; Niu, Hai; et al. (Frontiers in Pharmacology, 2023)
Severe acute pancreatitis (SAP) is a lethal gastrointestinal disorder, yet no specific and effective treatment is available. Its pathogenesis involves inflammatory cascade, oxidative stress, and autophagy dysfunction. Xanthohumol (Xn) displays various medicinal properties, including anti-inflammation, antioxidative, and enhancing autophagic flux. However, it is unclear whether Xn inhibits SAP. This study investigated the efficacy of Xn on sodium taurocholate (NaT)-induced SAP (NaT-SAP) in vitro and in vivo. First, Xn attenuated biochemical and histopathological responses in NaT‐SAP mice. And Xn reduced NaT‐induced necrosis, inflammation, oxidative stress, and autophagy impairment. The mTOR activator MHY1485 and the AKT activator SC79 partly reversed the treatment effect of Xn. Overall, this is an innovative study to identify that Xn improved pancreatic injury by enhancing autophagic flux via inhibition of AKT/mTOR. Xn is expected to become a novel SAP therapeutic agent.